(untitled) (Research, Society and Development, 2021)
Introduction: Among the restorative materials used in pediatric dentistry, amalgam, composite resin and more recently colored compomers stand out, the latter being quite popular among children, due to its presentation in colors such as blue, silver, pink, green, lemon and gold, which makes it more interesting to carry out treatments in this audience if compared to traditional methods, which in turn are the options of choice for parents. Objective: To evaluate the perception of children and their guardians regarding the use of different materials used for restorative procedures in pediatric dentistry. Material and method: Children and their respective parents or guardians were recruited from the Pediatric Dentistry clinic of the Centro Clínico Odontológico-Unipam, as well as from the private offices of Pediatric Dentists in Patos de Minas-MG. For the development of the research, a form aimed at both children and their parents/guardians was applied. This contained images, with the option to choose the preferred restorative material and a space to justify your preference. Results and Conclusion: The results of this research show that the determining factor for parents’ choice of restorative material is esthetics, with silver amalgam rejected by 100% and composite resin in the natural color of the teeth being the option for the majority. Children, on the other hand, have a different view of what is “ugly” or “beautiful”, especially those aged between 4 and 7 years old, who mostly opted for colored compomers.